Islamic Therapeutic Comunication Techniques of the Health Departement In Addressing Stunting in Serdang Bedagai Regency - Dalimunthe, Syah Ahmad Qudus; Lubis, Lahmuddin; Zainun, Zainun (Jayapangus Press, 2025)
Therapeutic communication is a form of communication that focuses on helping individuals overcome problems and achieve holistic well-being, including physical, emotional, and spiritual aspects. This study aims to explore Islamic therapeutic communication techniques applied by the Serdang Bedagai District Health Office in dealing with stunting problems. The research approach uses a qualitative method with data collection through interviews, observations, and documentation. Data sources consist of primary data, namely direct information from informants, and secondary data in the form of supporting documents. In dealing with stunting, the Serdang Bedagai District Health Office makes various efforts, such as providing education and understanding to the community. The goal is to strengthen the relationship between the health center and the local community. The forms of communication applied include interpersonal conversations and dialogues that are open and comfortable. This creates a sense of mutual trust between the community and the Health Office. The Islamic therapeutic communication techniques applied include verbal communication, such as the use of calming and empathetic words, and nonverbal communication, such as body language and supportive facial expressions. The conclusion of this study shows that Islamic therapeutic communication techniques play an important role in helping patients overcome health problems, especially stunting. Comfortable, open, and Islamic communication not only improves good relations between health workers and the community but also has a positive impact in supporting health programs in the area. This reflects a holistic approach that prioritizes the physical, emotional, and spiritual needs of patients.